After the fire - Rixon, Charlotte (Aria, 2024)
Ever since they first met at university, Beth and Nick have circled in and out of one another's lives: supporting each other through grief, marriage, divorce, career crises and family dramas. Fourteen years ago, when they were on the cusp of adulthood, they both survived a devastating fire that sent their lives in different directions. And they've been running ever since: from the pain, from the memories, and most devastatingly of all, from the guilt. But no matter how hard they try, there's something else they can't run from. The inescapable, terrifying truth: they're in love with each other. But how can they move forward, when neither of them can stop looking back?